Synthesis of a Self‐assembled Dual Morphologies Ag‐NPs/SrMoO4 Photocatalyst with LSPR Effect for the Degradation of Methylene Blue Dye. Issue 29 (1st August 2022) - Gu, Yufen; Guo, Bobo; Yi, Zao; Wu, Xianwen; Zhang, Jiao; Yang, Hua
Abstract: Morphology of photocatalyst has attracted many attentions due to its significant effect on photocatalytic properties. Herein, the effects of hydrothermal reaction conditions including time, temperature, and pH value on the morphology evolution as well as on the photocatalytic performance of SrMoO4 were investigated in detail. It was found that SrMoO4 had self‐assembled dual morphologies (spherical and dumbbell shape) under the specific reaction conditions with time=24 h, temperature=200 °C, and pH=6.13. In order to enhance its photocatalysis further, the silver nanoparticles (Ag‐NPs) were well‐dispersed uniform on the surface of as‐prepared samples to obtain Ag‐NPs/SrMoO4 composites by photoreduction method. It was determined that 3 %Ag‐NPs/SrMoO4 had the first‐class photocatalytic performance ( η =83.7 %, k app =0.05229 min ‐1 ) for the photodegradation of MB dye, which is ∼2.52 times that of the bare SrMoO4 with dual morphology ( η =51.9 %, k app =0.02078 min −1 ) by comparison with the apparent first‐order reaction rate constants. The photocatalytic performance was promoted by high efficiency of photo‐induced carriers' separation based on the effect of Localized Surface Plasmon Resonance (LSPR) of well‐dispersed Ag‐NPs. Abstract : Self‐assembled SrMoO4 with dual morphological was synthesized under specific reaction conditions. The effects of different hydrothermal conditions on the photocatalytic performance and microstructure of dual morphological SrMoO4 were systematically studied by the controlled variable method. The 3 % Ag‐NPs/SrMoO4 prepared by the photoreduction method has a first‐class photocatalytic performance for the photodegradation of MB dyes, which is about 2.52 times that of bare SrMoO4 . The localized surface plasmon resonance contributes to enhancing photocatalytic performance.